PENGARUH LATIHAN SWIM PARACHUTE DAN PADDLE TERHADAP KECEPATAN RENANG GAYA BEBAS 50 METER KU III 12-13 TAHUN BINATIRTA SWIMMING CLUB TAHUN 2025 - Jhon Olofman Sitompul; Mahmuddin; Zulfan Heri; Haris Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of swim parachute and paddle training on the speed of 50 Meter Freestyle Swimming Ku III 12-13 Years Binatirta Swimming Club in 2025. The sample was taken using a purposive sampling technique with a total of 8 athletes, the research instrument used was quantitative with an experimental method, while the data analysis technique used the Paired-Samples T-test method (Related T Test). The results of the t-test obtained a t-count value of 6.443 and t-table, namely the t-distribution table with α = 5% and df = 7 of 2.365. While the significance result is 0.000. Because t-count = 6.443 > t-table = 2.365 and the significance sig. (0.000) <α (0.05) then Ho is rejected and Ha is accepted, which means there is an effect of swim parachute and paddle training on the speed of 50 meter freestyle swimming ku III 12-13 years binatirta swimming club in 2025.